2010
DOI: 10.1051/0004-6361/200913403
|View full text |Cite
|
Sign up to set email alerts
|

Dust properties of protoplanetary disks in the Taurus-Auriga star forming region from millimeter wavelengths

Abstract: We present the most sensitive 3 mm-survey to date of protoplanetary disks carried out in the Taurus-Auriga star forming region (average rms of about 0.3 mJy), using the IRAM PdBI. With our high detection rate of 17/19 we provide the first detections at wavelengths longer than about 1 mm for 12 sources. This enables us to statistically study the mm SED slopes and dust properties of faint disks and compare them to brighter disks using a uniform analysis method. With these new data and literature measurements at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
369
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(408 citation statements)
references
References 75 publications
36
369
3
Order By: Relevance
“…Moreover, the very high surface density power-law exponent means that there is less mass in the outer regions of the disk. The outer disk radius of 500 AU used in this paper is significantly higher than the value of 100-300 AU adopted by Ricci et al (2010) to model the SED of SU Aur. Without knowing the true spatial extent of the disk, they showed that the submm and mm SED can be fitted with a very compact disk (R out ≈ 20 AU and i ≈ 70 • ), which highlights the importance of including the spatial information derived from the ExPo image in our analysis.…”
Section: Su Aur's Diskmentioning
confidence: 88%
“…Moreover, the very high surface density power-law exponent means that there is less mass in the outer regions of the disk. The outer disk radius of 500 AU used in this paper is significantly higher than the value of 100-300 AU adopted by Ricci et al (2010) to model the SED of SU Aur. Without knowing the true spatial extent of the disk, they showed that the submm and mm SED can be fitted with a very compact disk (R out ≈ 20 AU and i ≈ 70 • ), which highlights the importance of including the spatial information derived from the ExPo image in our analysis.…”
Section: Su Aur's Diskmentioning
confidence: 88%
“…To increase the accretion efficiency, smaller particles have to be accreted. Dust fragmentation (Birnstiel et al 2009) or radial diffusion (Ciesla 2009) may be promising mechanisms to retain mm-size particles in the (outer) disk, where they are observed on ∼Myr timescales (e.g., Lommen et al 2009;Ricci et al 2010).…”
Section: Significance To the Growth Of Pre-planetary Bodiesmentioning
confidence: 99%
“…When exactly such disks are formed and how they evolve through their early stages remain poorly understood (see, e.g., Li et al 2014, for a review). Well established disks around T Tauri stars or Class II young stellar objects have been widely reported and studied extensively (e.g., see Andrews et al 2009;Ricci et al 2010). Due to the low spatial resolution of the observations used in earlier studies, the emission from the disks in Class 0 and Class I sources have been mixed with the emission from the massive amounts of dust in the ambient protostellar envelope, making detection and characterization of disks in Class 0 sources very difficult (Jørgensen et al 2005a;Chiang et al 2008;Jørgensen et al 2009 cated Keplerian rotation being detected so far (Tobin et al 2012;Murillo et al 2013;Ohashi et al 2014;Lindberg et al 2014;Codella et al 2014).…”
Section: Introductionmentioning
confidence: 99%